Does the Direction of Kinesiology Tape Application Influence Muscle Activation in Asymptomatic Individuals? - Michelle Dolphin; Gary Brooks; Blair Calancie; Adam Rufa (International Journal of Sports Physical Therapy)
# Background Despite the popularity of tape among athletes and rehabilitation practitioners, there is controversy regarding the specific effects of kinesiology tape. Based on conflicting results and limitations of the literature, a well-designed study was desired to examine kinesiology tape application direction on muscle activation.